Genome analysis of colistin-resistant Salmonella isolates from human sources in Guizhou of southwestern China, 2019–2023 - Wu, Jingtong; Wen, Yongxian; You, Lv; Wei, Xiaoyu; Wang, Junhua; Zhu, Ge; Li, Shijun (Frontiers in Microbiology, 2025)
BackgroundColistin is commonly used as a last-resort antibiotic for multidrug resistance (MDR) bacterial infections. The emergence of colistin-resistant (CL-R) Salmonella has become a significant public health concern. However, the prevalence of CL-R Salmonella in Guizhou province remains unknown. Therefore, it is necessary to monitor CL-R Salmonella in Guizhou and systematically elucidate their characteristics-related resistance, virulence, and molecular epidemiology to develop effective public health strategies against resistant pathogens.MethodsThe CL-R Salmonella isolates were identified from 933 Salmonella isolates by antimicrobial resistance testing. To further evaluate the molecular epidemiology, the CL-R Salmonella isolates underwent whole-genome sequencing (WGS) analysis followed by bioinformatic analysis.ResultsA total of 43 CL-R isolates (4.6%) were identified from 933 Salmonella isolates, of which 39 isolates being MDR (resistance to three or more classes of antimicrobials). WGS analysis revealed 34 antibiotic resistance genes (ARGs), and point mutations in the gyrA gene (D87Y and D87G) were identified in all 43 CL-R isolates. Only one isolate carried the mcr-1.1 gene, a known colistin resistance. All CL-R isolates were found to carry multidrug efflux pumps. Furthermore, the most common resistance gene was aac(6′)-ly (40 out of 43), followed by blaTEM-1 (39 out of 43). The majority of CL-R isolates contained the virulence factor spvB and a notable diversity in other virulence factors with varied functions. Core genome multilocus sequence typing (cgMLST) revealed that 43 CL-R Salmonella isolates were divided into 19 cgSTs, with cgST179151 (10 out of 43) being the most prevalent. Additionally, the CL-R Salmonella isolates exhibited genetic similarities with human Salmonella isolates from Poland, Canada, and Zhejiang province. Among the 42 CL-R isolates lacking markers for CL-R, 12 single-nucleotide variations (SNVs) were observed in 24 isolates using genome-wide association study (GWAS) analysis, which was possibly associated with colistin resistance.ConclusionThis study revealed that the majority of CL-R Salmonella isolates in Guizhou province exhibited MDR, with complex resistance mechanisms, representing a significant public health challenge. The genetic similarities between isolates from Guizhou and other regions suggested the possibility of international transmission or shared reservoirs of resistance. These results highlighted the urgent need for enhanced surveillance and effective public health strategies to address the risks posed by these pathogens in Guizhou.